Studyholism: A New Obsessive-Compulsive Related Disorder? An Analysis of Its Association With Internalizing and Externalizing Features - Loscalzo, Yura; Giannini, Marco (Frontiers in Psychology, 2022)
Studyholism (or obsession with study) is a new potential OCD-related Disorder recently introduced in the literature. According to its theorization, there are two types of Studyholics: Engaged and Disengaged Studyholics, which are characterized, respectively, by high and low levels of Study Engagement. This study aims to shed light on the role of internalizing and externalizing features as antecedents and outcomes of Studyholism and Study Engagement. Moreover, it aims to analyze differences in psychopathology and sensation seeking between students demonstrating Disengaged and Engaged Studyholism. We performed four path analyses, MANOVAs, and Mann-Whitney tests on 1223 Italian college students (Mage = 22.56±3.53). Among the main findings, Studyholism is associated with psychological and academic impairment, while Study Engagement predicts better mental health and academic functioning. Though, the β values are lower for Study Engagement. Moreover, Studyholism is positively predicted by internalizing symptoms and negatively predicted by externalizing variables. Finally, students showing Engaged Studyholism have lower levels of Obsessive-Compulsive symptoms than those demonstrating Disengaged Studyholism. In conclusion, this study showed the critical importance of implementing preventive interventions aimed at reducing Studyholism levels in college students. Moreover, it provides support to the conceptualization of problematic overstudying as a new potential OCD-related disorder and to the value of distinguishing between Engaged and Disengaged Studyholics for tailored clinical interventions. Finally, it highlights the need to use two different theorizations and operationalizations for problematic overworking and overstudying. However, the literature on problematic overstudying is too scant to reach any firm conclusion. Hence, future studies should deepen the analysis of problematic overstudying, possibly using longitudinal designs, to unveil its internalizing and/or externalizing nature.